2021
DOI: 10.1111/csp2.509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of livestock guardian dogs on livestock predation in rural Mongolia

Abstract: Much like subsistence farmers the world over, Mongolian herders depend directly on their herds for food, materials, and income. Consequently, any loss of livestock through predation from wild carnivores (including wolves, foxes, snow leopards, and birds of prey) is a major challenge. With a lack of non‐lethal mitigation methods currently available to them, herders in Mongolia frequently manage conflict with predators with retaliatory hunting, negatively impacting populations of wild predators. Livestock guardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…As mentioned in section "Study Area, " many ecological conservation policies have been implemented in the Qinghai-Tibet Plateau since 2010. Therefore, this study compared whether the human pressure within KBAs and NNRs before and after 2010 had a statistically significant variation through a Wilcoxon signed-rank test, which has been widely used in ecological conservation research (Lieb et al, 2021). The Wilcoxon signedrank test is a nonparametric approach to test whether two groups of values are significantly different.…”
Section: Analysis Of Human Pressure Changes After the Implementation ...mentioning
confidence: 99%
“…As mentioned in section "Study Area, " many ecological conservation policies have been implemented in the Qinghai-Tibet Plateau since 2010. Therefore, this study compared whether the human pressure within KBAs and NNRs before and after 2010 had a statistically significant variation through a Wilcoxon signed-rank test, which has been widely used in ecological conservation research (Lieb et al, 2021). The Wilcoxon signedrank test is a nonparametric approach to test whether two groups of values are significantly different.…”
Section: Analysis Of Human Pressure Changes After the Implementation ...mentioning
confidence: 99%
“…2018 ). Several studies have evaluated their behavior and effectiveness after integration into the herd ( Coppinger et al 1988 ;Andelt 1992 ;Espuno et al 2004 ;Gehring et al 2010b ;Rigg et al 2011 ;van Bommel and Johnson 2012 ;Marker et al 2021 ;Lieb et al 2021 ). Of these, most studies support their efficacy in reducing losses caused by various predators, both solitary ( Woodroffe et al 2007 ;Marker et al 2021 ) and social predator species ( van Bommel and Johnson 2012 ;Lieb et al 2021 ), to livestock, although the values may vary ( Miller et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated their behavior and effectiveness after integration into the herd ( Coppinger et al 1988 ;Andelt 1992 ;Espuno et al 2004 ;Gehring et al 2010b ;Rigg et al 2011 ;van Bommel and Johnson 2012 ;Marker et al 2021 ;Lieb et al 2021 ). Of these, most studies support their efficacy in reducing losses caused by various predators, both solitary ( Woodroffe et al 2007 ;Marker et al 2021 ) and social predator species ( van Bommel and Johnson 2012 ;Lieb et al 2021 ), to livestock, although the values may vary ( Miller et al 2016 ). Bruns et al (2020) , on the basis of a review of 30 studies (7 focused on LGDs), found they had the highest variation in effectiveness when compared with other measures (calving control, deterrents, fencing, herding, lethal control, mixed measures, and translocation), ranging from an increase of depredation by 23.3% to a decrease by 100%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although wolves have been less commonly reported as having rabies within Mongolia, they are estimated to be the source of rabies infection in 73.1% of small ruminant cases, 12.6% of equine cases and 32.4% domestic canine cases (Odontsetseg et al, 2009). The enhanced contribution of rabies cases despite lower amounts of rabies reports may reflect both the reported higher frequency with which wolves prey on domestic animals and their widespread distribution across the country (Augugliaro et al, 2020; Lieb et al, 2021; Salvatori et al, 2021).…”
Section: Introductionmentioning
confidence: 99%